Motor Listrik 3 Fasa Sebagai Sistem Penggerak Motor Roll Pada Mesin Case Sealer di Pt. Matahari Megah - Muhammad Iqbal Naufal; Irwanto Irwanto (Jurnal Sains dan Teknologi, 2023)
The electric motor is a system that plays an important role in the operation of production machines in the industrial world. The advantages of a 3 Phase Electric Motor are that it is economical, uses a strong construction and has high efficiency. In order to carry out its functions properly, this drive system is equipped with various other electrical equipment to synergize with each other so that the case sealer machine can function optimally and always prioritize periodic maintenance. The drive system used is a 3-phase electric motor which functions to move the motor roll so that the product to be packaged in the case sealer machine can run.